2016
DOI: 10.18553/jmcp.2016.22.8.901
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2013 Cholesterol Guideline on Patterns of Lipid-Lowering Treatment in Patients with Atherosclerotic Cardiovascular Disease or Diabetes After 1 Year

Abstract: No outside funding supported this research. Chan is supported by grants from the National Heart Lung and Blood Institute (1R01HL123980 and K23HL102224). Tran, Stockl, Lew, and Solow are employed by Optum. Kao and Caglar were employed by Optum when this study was conducted. Chan serves as an advisor and consultant to OptumRx but received no compensation for work on this manuscript. Stockl is also employed by the Journal of Managed Care & Specialty Pharmacy. Spertus reports personal fees from United Healthcare a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 23 publications
5
28
2
Order By: Relevance
“…The modest effect of the ACC/AHA guideline change on statin prescribing we observed is consistent with some recent reports that the ACC/AHA guideline change was associated with either a negligible (Tran et al. ) or small (Rodriguez et al. ; Pokharel et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The modest effect of the ACC/AHA guideline change on statin prescribing we observed is consistent with some recent reports that the ACC/AHA guideline change was associated with either a negligible (Tran et al. ) or small (Rodriguez et al. ; Pokharel et al.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the large decline in use of simvastatin during the preformulary period, though not a central focus of our analysis, is temporally associated with the FDA's June 2011 "black box" warning regarding use of high-dose simvastatin (Food and Drug Administration 2011), a finding consistent with some studies of previous drug-specific FDA regulatory warnings (Dorsey et al 2010;Dusetzina et al 2012). The modest effect of the ACC/AHA guideline change on statin prescribing we observed is consistent with some recent reports that the ACC/AHA guideline change was associated with either a negligible (Tran et al 2016) or small Pokharel et al 2017) change in the use of statins and nonstatin lipid-lowering drugs. A study in the VA found somewhat larger changes in statin use but did not include all high-risk patients, was limited to 6 months of postguideline data, and did not adjust for underlying trends in statin use .…”
Section: Discussionsupporting
confidence: 89%
“…This rate of adherence to guidelines is in-line or slightly above previously published estimates of statin use in nationally representative managed care populations. 5,9 Our chart review analysis builds on previous publications that rely on physician surveys to understand observed statin treatment patterns. 10,11 By evaluating the reasons behind therapeutic decisions documented in the notes of the prescribing physician, which is not typically available through traditional database analyses, our study provides essential information needed to better understand statin prescribing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…At the time the guidelines were published, projections indicated that they would greatly expand the pool of patients who qualify for statin therapy, thereby increasing the use of statins 8, 10. We examined over 90 000 patients before and after the guidelines release and found that overall statin use decreased following the release of the guidelines.…”
Section: Discussionmentioning
confidence: 99%